THE RELATIONSHIP BETWEEN CUSTOMARY LAW AND ISLAMIC LAW IN PAPUAN MARRIAGE PRACTICES - ansar, lukman; Sylviah; Zulfadli; Podu, Sabar; Tarmizi (Jurnal Ar-Risalah, 2025)
This article examines the customary marriage practices of the Papuan people from the perspective of Islamic law within the framework of legal pluralism. Marriage in Papuan society is not only understood as an individual bond between a man and a woman, but also as a social event involving extended families, clans, and customary structures. In practice, the fulfillment of customary requirements often becomes the main basis for the legitimacy of marriage, while the marriage contract according to Islamic law is carried out simply or even neglected. This condition reflects the dominance of customary law as a living law that is deeply rooted in the social structure of society. Through a juridical-empirical approach with normative and socio-anthropological analysis, this study shows that the relationship between customary law and Islamic law is negotiable and contextual. Islamic law is recognized theologically, but its application is often adjusted to the interests of customary social harmony. The findings of the study also reveal the serious implications of customary marriage practices for the protection of women and children, especially when the marriage is not accompanied by a marriage contract that is valid according to Islamic law. This article emphasizes that customary marriage practices in Papua cannot be viewed solely as an expression of culture, but also as a matter of justice and legal protection. Therefore, a model for strengthening Islamic law that is sensitive to the customary context is needed, without neglecting the basic principles of justice and public interest.